Some computational aspects of Gaussian CARMA modelling - Helgi Tómasson (Institute for Advanced Studies (IHS), 2011)
Representation of continuous-time ARMA, CARMA, models is reviewed. Computational aspects of simulating and calculating the likelihood-function of CARMA are summarized. Some numerical properties are illustrated by simulations. Some real data applications are shown.
Keywords: C01; C10; C22; C53; C63; 330; CARMA; maximum-likelihood; spectrum; Kalman filter; computation